IMPROVING STUDENTS ABILITY ON ENGLISH FOR SPECIFIC PURPOSE (ESP) COURSE THROUGH STAR 7 JUMPS MODEL AT COACH STUDY PROGRAM FKIP- UNRI - Erni (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This classroom action research design was aimed at analysing students’ failure in learning ESP (English for Specific Purposes) and finding out its solution. The purpose of this study was to improve the ability of Coach Study Program students of FKIP UNRI in learning ESP through the STAR 7 Jumps model and to find out factors that contribute more to the improvement. A total of 36 students, consisting of 27 boys and 9 girls, were involved as the participants of the study. This research was done in two cycles. Designing syllabus, evaluating teaching materials, and compiling teaching materials were also the procedures done in each cycle (planning, action, observation, and reflection). Semi-structured observation sheets and field notes were used to identify how the lecturer taught and how the learners learned, and an ESP achievement test was employed to identify students’ ability. The lecturer applied the seven steps of STAR well, which made the students more active, motivated, and interested in learning ESP. Students’ ability in learning ESP also improved, where the mean pre-test was 67, mean post-test cycle 1 was 73, and mean post-test cycle 2 was 76. The most dominant factor that caused the improvement was the teaching materials about the match sports topic, by which most students were active in problem identification, brainstorming, analyzing and formulating problems, self-study, and presentation.